Analisis Penerapan Sistem dan Prosedur Surat Perintan Membayar Uang Persediaan (SPM-Up) Badan Pengelolaan Keuangan dan Aset Daera Kabupaten Pulau Morotai - Ardin Umar; Irwan Moi (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research aims to find out: (1) The implementation of the Perintan system and procedures to pay the money for the supply (SPM-Up) at the financial management body and regional assets of the District government of Morotai Island; (2) Implementation of the Perintan system and procedures to pay the money for the supply (SPM-Up) at the financial management and regional assets of Morotai Island District Government. The subject of this study is the Kabid treasurer of regional general and Treasurer expenditure agency for financial and regional government assets Morotai Island Regency. Data is collected by interview methods, observations and documentation of research subjects. Results showed that: (1) Kabid Treasurer General District and Treasurer of expenditure on the Board of Financial and regional assets management has been the system and procedure of Perintan pay money supply (SPM-Up) in accordance with the applicable guidelines, from The initial stages of collecting the transaction evidence to the extent of ratification and submission to the relevant parties; (2) Treasurer of expenditure and Kabid treasurer of regional general on financial management and regional assets of Morotai Island District government has implemented an administration and accountability system in accordance with the applicable guidelines, from Bookkeeper's shopping to the breakdown of the Perintan letter procedure to pay money supply (SPM-Up).